LANDASAN PENGEMBANGAN KURIKULUM 2013 - Rahmatullah Rahmatullah (Ta`Limuna: Jurnal Pendidikan Islam, 2013)
This paper will discuss the foundation for curriculum development. Curriculum change and development is not inevitable, it is motivated by a shift in perspective, the changing times, changes and developments in technology, changes in social and cultural community and others. Curriculum development and change is intended to better purpose than the previous curriculum. Foundations of curriculum development at least include some things like grounding sociological, philosophical foundation, the cornerstone of religion in Islamic education and others. Some of the foundation should be sufficiently represent the fundamentals of curriculum development, curriculum development as for the foundation in 2013 has included some of the above plus the foundation juridical foundation that has been set by the government.